CHA1 in Managment of Triple-Negative Breast Cancer - Alamoudi, Mariam. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: Amy Yee.; Committee: James Baleja, David Greenblatt, and Eric Paulson.; Keyword: Pharmacology.